Suppression of lncRNA Gm47283 attenuates myocardial infarction via miR-706/ Ptgs2/ferroptosis axis. Issue 4 (1st April 2022) - Gao, Feng; Zhao, Yongcheng; Zhang, Bin; Xiao, Chunwei; Sun, Zhanfa; Gao, Yuan; Dou, Xueyong
ABSTRACT: Myocardial infarction (MI) is the leading cause of sudden death. Long non-doing RNAs (lncRNAs) were demonstrated to play crucial roles in multiple diseases, including cancer and cardiovascular diseases. Nevertheless, the molecular mechanism of lncNRAs in MI is unclear. In this study, we integrated bioinformatics and molecular biological experiments to identify the novel lncRNA transcripts and elucidated its regulatory mechanism in MI. First, we identified 10 dysregualted lncRNAs and found that lncRNA Gm47283 was the top risk factor in MI. Bioinformatics analysis predicted that lncRNA Gm47283 exerted function via targeting miR-706 and Ptgs2. Ptgs2 was also the known regulator of ferroptosis. Inhibition or overexpression of lncRNA Gm47283 could regulate Ptgs2 expression and downstream ferroptosis activity. Overexpression of miR-706 could inhibit the expression of Ptgs2 and the activity of ferroptosis, thereby attenuated cellular injury. Mechanically, co-transfection experiments showed that overexpression of miR-706 could reverse the damage effect that was caused by lncRNA Gm47283 overexpression, via inhibiting Ptgs2 and ferroptosis. Additionally, inhibition of lncRNA Gm47283 by stem cell membrane coated siRNA could attenuate MI in vivo . Our study elucidated a novel mechanism containing lncRNA Gm47283 / miR-706 / Ptgs2 /ferroptosis in MI, which provided a potential therapeutic for MI. Graphical Abstract. Stem cell membrane coated siRNA of lncRNA Gm47283 inhibits cardiomyocyte ferroptosis in myocardial infarction rat. Stem cell membrane-coated siRNA of lncRNA Gm47283 increases miR-706, and then miR-706 suppresses the expression of Ptgs2 to reduce lipid peroxidation toxicity, and then inhibits cardiomyocyte ferroptosis. PUFA: polyunsaturated fatty acid. Graphical Abstract: uf0001